Validation of the extended version of the Dissociative Experiences Scale (DES) in patients diagnosed with substance use disorders. (4th July 2022) - Gidzgier, Piotr; Driessen, Martin; Gawęda, Łukasz; Havemann-Reinecke, Ursula; Wedekind, Dirk; Lüdecke, Christel; Ohlmeier, Martin; Weirich, Steffen; Kemper, Ulrich; Reis, Olaf; Schneider, Udo; Schäfer, Ingo
ABSTRACT: Background: The most extensively used instrument to measure dissociation is the Dissociative Experiences Scale (DES). Recently, an extended version of this instrument was provided, which also measures somatoform symptoms of dissociation. The aim of this study was to examine the component structure and internal consistency of the extended version of the Dissociative Experiences Scale (FDS) in patients diagnosed with substance use disorders (SUD). Methods: Principal component analyses (PCAs) were conducted in a large clinical sample of patients diagnosed with SUD ( n = 459) for the 44 FDS items, the 28 original DES items, the 23 items of the original DES subscales that compose FDS subscales of amnesia, absorption, and depersonalization/derealization, and the 9 conversion subscale items. Results: PCA of all 44 FDS items yielded a 9-factor solution where the first factor explained 32% variance. A 6-, 4-, and 2-factor solution, respectively, was found for 28 DES original items, 23 items of original DES subscales that compose FDS subscales of amnesia, absorption, and depersonalization/derealization, and 9 items of the conversion subscale of the FDS. Conclusion: FDS proves to be a reliable tool that can be used to screen patients with SUD for dissociative psychopathology within the ICD and DSM-5 framework.